Alternative Water Supply Systems - Memon, Fayyaz Ali; Ward, Sarah (IWA Publishing, 2014)
Owing to climate change related uncertainties and anticipated population growth, different parts of the world (particularly urban areas) are experiencing water shortages or flooding and security of fit-for-purpose supplies is becoming a major issue. The emphasis on decentralized alternative water supply systems has increased considerably. Most of the information on such systems is either scattered or focuses on large scale reuse with little consideration given to decentralized small to medium scale systems. Alternative Water Supply Systems brings together recent research into the available and innovative options and additionally shares experiences from a wide range of contexts from both developed and developing countries. Also covered are the technical, social, financial and institutional aspects associated with decentralized alternative water supply systems. These include systems for greywater recycling, rainwater harvesting, recovery of water through condensation and sewer mining.